Analisis Kredit Investasi dan Pengaruhnya terhadap Laba Operasional - Ratna, Ratna (Jurnal Aplikasi Manajemen, 2009)
This research have goals to know investment credit regular for small industry to increase operational benefit and to know haw big investation credit have influence on operational benefit. This research use kuantitative methods with linier regression and for UD Batu Permata have Y = 11.282.180 + 2,801x with (RÂ²) = 0,764, this resume description that invesment credit can inference operational benefit 76,4 % an influence by another variabel 23,6 %. Based on that invesment credit must be decreasef and according to industry/firm need because it can be re-used.Keywords: investation credit and operational benefit